1997
DOI: 10.1523/jneurosci.17-13-05136.1997
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Right Anterior Temporal Lobe in Taste Quality Recognition

Abstract: We conducted two experiments to examine central processing of the taste of citric acid. In the first experiment, elevated citric acid recognition thresholds, but normal detection thresholds, were observed in a group of patients who had undergone a right anterior temporal lobectomy for the treatment of epilepsy, compared with a control group and a group of patients who had undergone the same operation in the left hemisphere. In the second study, using positron emission tomography, we compared regional cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(69 citation statements)
references
References 45 publications
6
62
0
1
Order By: Relevance
“…Although there has been considerable controversy surrounding the potential laterality of chemosensory systems, with some studies suggesting right hemisphere dominance (Barry et al 2001;Savic and Berglund 2000;Small et al 1997bSmall et al , 1999Zatorre et al 1992) and others suggesting that laterality may depend on handedness Royet et al 2003) or affective valence (Anderson et al 2003;Pardo 1997, 2000;Zald et al 1998), it is striking that the activity we observed in the anterior ventral insula/caudal OFC occurred only in the right hemisphere. This asymmetry remained when the t-map threshold was dropped to P Ͻ 0.1.…”
Section: Lateralitymentioning
confidence: 56%
“…Although there has been considerable controversy surrounding the potential laterality of chemosensory systems, with some studies suggesting right hemisphere dominance (Barry et al 2001;Savic and Berglund 2000;Small et al 1997bSmall et al , 1999Zatorre et al 1992) and others suggesting that laterality may depend on handedness Royet et al 2003) or affective valence (Anderson et al 2003;Pardo 1997, 2000;Zald et al 1998), it is striking that the activity we observed in the anterior ventral insula/caudal OFC occurred only in the right hemisphere. This asymmetry remained when the t-map threshold was dropped to P Ͻ 0.1.…”
Section: Lateralitymentioning
confidence: 56%
“…Although the cerebellum is not traditionally considered part of the olfactory system, cerebellar activity has been consistently observed in functional imaging studies of olfaction (Small et al, 1997;Yousem et al, 1997;Sobel et al, 1998;Qureshy et al, 2000;Savic et al, 2000;Zatorre et al, 2000;Cerf-Ducastel and Murphy, 2001;Ferdon and Murphy, 2003). Despite this, the pathways through which olfactory information reaches the cerebellum and the functional role of the cerebellum in olfaction remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous neuroimaging studies of the representation of taste in human brain have found cortical areas reacted to taste such as the frontal operculum/insula and the orbitofrontal cortex [14][15][16]. Furthermore, many neuroimaging studies have shown right-hemispheric dominance is involved in both taste perception [17,18] and recognition [14] of gustatory stimuli, while some studies have shown bilateral or left-lateral areas of human brain are concerned with the quality of taste [19,20]. Our finding supported that the lateral PFC, especially the right hemisphere, are acutely The channels which were truly evoked by sweet and sour tastes were used to compare, and all of them showed different levels significantly.…”
Section: Discussionmentioning
confidence: 99%